The provisional status of arthropod inventories in the Macaronesian islands - Lobo, Jorge M. (2010)
"[...]. We examined the available data on the most hyper-diverse group of terrestrial animals (the arthropods) with the aim to assess the general reliability of these Macaronesian inventories. First, we describe the main differences between archipelagos in the year of species description. These calculations allow us to compare the temporal pattern of the taxonomic process in the four archipelagos depending on the origin and range size of the species. Subsequently, we examine the shape and characteristics of discovery curves in order to obtain a provisional picture of the taxonomic completeness of current inventories and the amount of work that still needs to be completed. Lastly, we discuss the implications of our results on our current knowledge of Macaronesian arthropods for each archipelago." (da Introdução)